Exploring Instagram at 2025: The Morphosyntactic Relationship between Indonesian and Dutch - Dimas Maulana Firdaus (PRASASTI: Journal of Linguistics, 2026)
This research investigates the morphosyntactic constructions underlying the semantic relations between the Indonesian and Dutch languages, based on the linguistic practices observed on Instagram. Embedded in their common past of colonialism, the two languages have had reciprocal impact on various elements of the lexicon, the syntax, and semantics. This study adopts a qualitative research paradigm in conjunction with a Systematic Literature Review (SLR) in order to examine linguistic structures and evolution evidenced in user-generated Instagram posts and observations derived from academic journals, online media, and linguistic discussions on the internet. This aims to uncover morphosyntactic parallels and contact-induced semantic changes wrought by social media communication. Situated within the frameworks of morphosyntax and historical linguistics, the present research illustrates how social media platforms like Instagram can be fertile grounds for analysis of modern cases of postcolonial language contact.